2018
DOI: 10.1159/000494656
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B-Mediated NLRP3 Inflammasome Formation and Activation in Angiotensin II -Induced Hypertensive Mice: Role of Macrophage Digestion Dysfunction

Abstract: Background/Aims: Angiotensin II (Ang II) is an octapeptide hormone that plays a significant role in mediating hypertension. Although hypertension is considered a chronic inflammatory disease, the molecular basis of the sterile inflammatory response involved in hypertension remains unclear. Methods: We investigated the role of macrophage NLRP3 inflammasomes in engulfing and digesting microbes, a key macrophage function, and in early onset of hypertension-associated macrophage injury using biochemical analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Thus, fibrillar Aβ interacts with TLRs to promote the transcriptional priming of the NLRP3 inflammasome through NF-κB activation. Then, ROS, cathepsin B, and other metabolites released upon lysosomal damage induce the activation and oligomerization of the inflammasome [ 221 , 222 , 223 ]. NLRP3-mediated IL-1β production triggers the release of downstream inflammatory cytokines and neurotoxic factors.…”
Section: Age-associated Diseases: Implication Of the Nlrp3 Inflammmentioning
confidence: 99%
“…Thus, fibrillar Aβ interacts with TLRs to promote the transcriptional priming of the NLRP3 inflammasome through NF-κB activation. Then, ROS, cathepsin B, and other metabolites released upon lysosomal damage induce the activation and oligomerization of the inflammasome [ 221 , 222 , 223 ]. NLRP3-mediated IL-1β production triggers the release of downstream inflammatory cytokines and neurotoxic factors.…”
Section: Age-associated Diseases: Implication Of the Nlrp3 Inflammmentioning
confidence: 99%
“…The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome is a multi-protein complex comprising NLRP3, PYD and CARD domains that contain pro-caspase-1, which has been found to serve a role in UC ( 8 ). The NLRP3 inflammasome is stimulated by a diverse series of agonists (such as ATP and UV radiation, and pattern-associated molecular patterns derived from bacteria, virus, fungus, and protozoa) ( 9 ), before activates caspase-1, which results in the maturation of the proinflammatory cytokine IL-1β ( 10 ). It was previously reported that the activation of NLRP3 inflammasome served an inflammatory role in dextran sulfate sodium (DSS)-induced colitis ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ang II can cause NLRP3 inflammasome activation by promoting endoplasmic reticulum stress and release of cathepsin B. 32,33 Activated NLRP3 inflammasome causes cell damage, mitochondrial dysfunction, smooth muscle phenotypic transformation and vascular remodeling, causing abnormalities in tissues and organs. 34,35 Some studies have shown that the effects of angiotensin-converting enzyme inhibitors or ARBs on diabetes may be achieved through the Caspase pathway.…”
Section: Discussionmentioning
confidence: 99%